Development of GIS-based ground flash density and its statistical analysis for lightning performance evaluation of transmission lines in Peninsular Malaysia - Roslan, Nurzanariah; Ungku Amirulddin, Ungku Anisa; Ab. Kadir, Mohd Zainal Abidin; Abdullah, Noradlina (Universiti Putra Malaysia Press, 2024)
Malaysia is one of the world's highest lightning regions, making it an ideal location for studying lightning activities, as they cause many power outages on overhead transmission lines. This study presents ground flash density (GFD) mapping and statistical analysis of lightning flash data in Peninsular Malaysia, which will be used to evaluate the lightning performance of transmission lines. Using Geographical Information System (GIS) software, the GFD map and lightning flash data for statistical analysis were extracted. MATLAB was then used to perform statistical analysis and obtain the probability of peak lightning current using the generalized extreme value (GEV) distribution. This study analyzed six years of lightning flash data from 2012 to 2017 recorded by the Lightning Location System (LLS) and used the Peninsular Malaysia base map from the Department of Survey and Mapping Malaysia (JUPEM). Results show that the GFD mapping approach effectively classifies GFD distribution and identifies areas with high lightning activity. 81 of 4,536,380 lightning flashes were negative polarity, with a higher mean peak current magnitude than positive ones. More lightning activity was observed during the Southwest Monsoon (June-September) and the first Inter-Monsoon season (April-May). Pahang had the most lightning flashes due to its large land area. The GFD map overlaid on the transmission line demonstrated how lightning performance on the transmission line can be assessed. These findings are useful for utility and protection engineers to improve the performance of transmission lines.